Penerapan Syarat-Syarat Bagi Gembala Jemaat Berdasarkan Kitab 1 Timotius 3:1-7 - Yoel Benyamin (Predica Verbum: Jurnal Teologi dan Misi, 2022)
The requirements as a church pastor in the book of 1 Timothy 3:1-7 are very relevant to the life of the church today in determining the pastor of the church. This application by the local church is very useful in finding a qualified church pastor according to Bible values. This article appears based on text research conducted with the method of grammatical study which finally found biblical truth about the requirements for church pastors. This grammatical study uses library research methods that rely on scientific references, credible books and online articles. The author finds that the values ​​that Paul conveyed to Timothy can be a reference for appointing a pastor in the local congregation. The implication obtained based on text research is that a church pastor must comply with the conditions taught by the apostle Paul, physically and spiritually.